Cover Picture: Size‐Controlled Formation of Noble‐Metal Nanoparticles in Aqueous Solution with a Thiol‐Free Tripeptide (Angew. Chem. Int. Ed. 30/2016). Issue 30 (20th May 2016) - Corra, Stefano; Lewandowska, Urszula; Benetti, Edmondo M.; Wennemers, Helma
Abstract : Monodisperse noble‐metal nanoparticles (in the example, PdNPs) can be formed in aqueous solution in the presence of a thiol‐free tripeptide, as shown by H. Wennemers and co‐workers in their Communication onpage 8542 ff. The picture illustrates how, upon complexation to Pd 2+ ions and their reduction to Pd 0, the peptide controls nanoparticle generation by forming a compact peptidic coat around the metal core.